Space efficiency study on the physical configuration of top most visited frontline government service offices in General Santos City - Maceda, Nicole Kate B.; Ylagan, Myrafe S. (2020)
Planning and designing office spaces, especially government buildings are-always bounded by standards. There are several issues present in most of the front line government agencies in General Santos City, including here are: poor space coordination, difficulty in transaction and lack of facilities inside the office building. This research analyzed both physical and operational constraints of the offices by understanding how it affects the space efficiency of the spaces.This study focused on articulating new guidelines to achieve space efficient offices by collecting data that could determine the factors affecting the efficiency of the spaces. The researcher used Fuzzy Logic Simulation Method.The simulation consists of fuzzy rules in word form that each corresponds to a numerical score. The government agencies that were studied are: LTO, SSS,PRC, PSA, HDMF, PHIC, and LRA. The results of the simulation are analyzed to better understand how the architectural issues affect the efficiency of the space.The proposed project translation was derived from the results of the study.The concept of ?one-stop-shop? will branch the highly visited government agencies into one complex.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020